Aspectos tafonômicos e paleoecológicos das paleoentomofaunae das formações Crato e Fonseca - Oliveira, Francisco Irineudo Bezerra de (2023)
In the past few years, the development of technology has made a variety of analytical tools available. Geoscientists have taken advantage of these innovations to expand our knowledge of the planet's past. At the core of this progress, disciplines such as Paleobiology, Paleoecology and Taphonomy have benefited from these advances to conceive new discoveries regarding the biological and geological history of past organisms and ecosystems. In this context, Lagerstätten-type deposits played a prominent role in discussions regarding new findings involving the preservation of soft tissues in the fossil record. The aim of this thesis is to shed light on the taphonomic and paleoecological processes involved in the preservation of paleoenthomofauna from the Crato (Lower Cretaceous of Ceará) and Fonseca (Eocene-Oligocene of Minas Gerais) formations. For this purpose, a combination of techniques were employed such as Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Spectroscopy (EDS), Fourier Transform Raman Spectroscopy (FT Raman), Near Infrared Spectroscopy by Transform Fourier (FTIR) and various statistical procedures. These tools were used to characterize the articulation of the individuals, the preservation fidelity of the cuticular tissues, the mineralogy and the chemical composition of the specimens in macro and micrometric scales. Here, the results represent the first taphonomic study carried out on the paleoentomofauna of the Fonseca Formation. In contrast to the still little-known paleoentomofauna of the Fonseca Formation, the paleoentomofauna of the Crato Formation is world famous for the beauty and abundance of its fossils. This document attested that the pyritized (mineralized) insects of Crato Fm. appear with a higher degree of preservation than the kerogenized ones. This data differs from other similar studies available in the literature. In general, pyritized carcasses spend much more time within the zone of anaerobic bacterial respiration (sulfate reduction) which is less favorable for preservation of labile tissues than the methanogenesis zone. Crato insects show different aspects related to post-diagenetic aspects since mineralized insects are more affected by telodiagenetic processes. Mineralized and partially articulated insects are preferentially preserved by goethite. In contrast, mineralized and articulated insects are preferentially preserved by hematite. In this study, 1.135 insects from the pale and bluish limestones of Crato Fm. were analyzed, included in 55 different families, to measure their ecological (abundance, distribution) and biostratinomic (interaction with the paleoenvironment) relevance. This study shows a higher number of aquatic and semi- aquatic insects preserved in a dorsoventral position in pale limestones. In contrast, the bluish limestones mostly record terrestrial insects, where individuals are proportionately more disarticulated than the insects preserved in pale limestones. This finding indicates that insects from bluish limestones underwent more rework in the biostratinomic phase. Compared to other Early Cretaceous paleoentomofaunae, the taxonomic literature for Crato paleoentomofauna is markedly different. While other preserved paleoentomofaunae in the Yixian (China) and Zaza (Russia) formations are dominated by Coleoptera and Hymenoptera species, Crato Fm. records relatively fewer species from these groups and is relatively richer in Paleoptera (Odonata) species.